Association and enlightenment : Scottish clubs and societies, 1700-1830 - Wallace, Mark C.; Rendall, Jane, 1945-; Whatley, Christopher A.; Rendall, Jane; Whatley, Christopher A.; Allan, David; Harris, Bob; Jenkinson, Jacqueline; McLean, Ralph; Caudle, James J.; Brown, Rhona; Andrews, Corey (Studies in Eighteenth-Century Scotland Ser., 2021)
"Social clubs as they existed in eighteenth- and early nineteenth-century Scotland were varied: they could be convivial, sporting, or scholarly, or they could be a significant and dynamic social force, committed to improvement and national regeneration as well as to sociability. The essays in this volume--the first full-length study of the subject in fifty years-examine the complex history of clubs and societies in Scotland from 1700 to 1830. Contributors address attitudes toward associations, their meeting-places and rituals, their links with the growth of the professions and with literary culture, and the ways in which they were structured by both class and gender. By widening the context in which societies are set, this volume offers a new framework for understanding them, bringing together the inheritance of the Scottish past, the unique and cohesive polite culture of the Scottish Enlightenment, and the broader context of associational patterns common to Britain, Ireland, and beyond"--